Quantum dot material, quantum dot patterning method and quantum dot light-emitting device

By using hydrogen intercalation reaction between thioanthone groups and oleic acid ligand in quantum dot photoresist, crosslinking of quantum dot films is achieved, solving the problem of reduced conductivity caused by resin adhesives and easy quantum dot fall off , improves film thickness uniformity and luminous efficiency, and meets the requirements of high-resolution full-color display.

CN119220261APending Publication Date: 2024-12-31YUNGU GUAN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310798522.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The addition of resin to the existing quantum dot photoresist materials as adhesives leads to a decrease in conductivity, thereby reducing luminous efficiency. In addition, quantum dots are prone to fall off during the patterning process, affecting film thickness uniformity and optical properties.

Method used

Quantum dot material including the first quantum dot body, the second quantum dot body, the oleic acid ligand and the photosensitive group, the photosensitive group is a thioanthone group, and the oleic acid ligand is inserted under ultraviolet light irradiation. The hydrogen reaction realizes cross-linking of adjacent quantum dot bodies, forming a stable quantum dot film, avoiding the use of resin adhesives.

Benefits of technology

The high resolution and film thickness uniformity of the quantum dot film are achieved, the luminous efficiency is improved, and the high pixel density is ensured, meeting the needs of high-resolution dynamic full-color display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220261A_ABST
    Figure CN119220261A_ABST
Patent Text Reader

Abstract

The invention provides a quantum dot material, a quantum dot patterning method and a quantum dot light-emitting device.The quantum dot material comprises a first quantum dot body, a second quantum dot body, an oleic acid ligand and a photosensitive perssam.The oleic acid ligand is connected to the first quantum dot body and / or the second quantum dot body, and the photosensitive perssam.The oleic acid ligand is connected to the first quantum dot body and / or the second quantum dot body. The photosensitive group is connected to the first quantum dot body and / or the second quantum dot body, the first quantum dot body and the second quantum dot body are respectively at least connected with one of the oleic acid ligand and the photosensitive group, and the photosensitive group is a thioxanthone group. A quantum dot pattern prepared from the quantum dot material is good in film thickness uniformity and high in resolution, and quantum dot patterning can be achieved while high pixel density is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of quantum dot materials, and in particular relates to a quantum dot material, a quantum dot patterning method and a quantum dot light-emitting device. Background Art

[0002] The light-emitting layer of quantum dot light-emitting diodes is the quantum dot layer, and the precise preparation of the sub-pixel area of ​​quantum dot light-emitting diodes is a prerequisite for achieving high-resolution dynamic full-color display, which requires precise patterning of the quantum dot light-emitting layer.

[0003] Therefore, it is necessary to develop a photolithographic quantum dot material to meet the requirements of preparing quantum dot patterns with good film thickness uniformity and high resolution. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a quantum dot material, a quantum dot patterning method and a quantum dot light-emitting device. The quantum dot material includes a first quantum dot body, a second quantum dot body, an oleic acid ligand and a photosensitive group. The quantum dot material can be cross-linked under ultraviolet light irradiation conditions to ensure high pixel density while achieving quantum dot patterning.

[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a quantum dot material, comprising a first quantum dot body, a second quantum dot body, an oleic acid ligand and a photosensitive group, wherein:

[0007] The oleic acid ligand is connected to the first quantum dot body and / or the second quantum dot body, the photosensitive group is connected to the first quantum dot body and / or the second quantum dot body, the first quantum dot body and the second quantum dot body are respectively connected to at least one of the oleic acid ligand and the photosensitive group, and the photosensitive group is a thioxanthone group.

[0008] In the present invention, the thioxanthone group is a photosensitive group, so that the prepared quantum dot film can be photolithographic; the thioxanthone group can extract hydrogen under light, and undergo a hydrogen insertion reaction with the oleic acid ligand, which can achieve cross-linking of adjacent quantum dot bodies. Due to the occurrence of cross-linking, the quantum dot material is evenly and stably distributed on the substrate. The quantum dot material of the present invention forms a stable quantum dot film through photolithography without adding resin as an adhesive, realizes quantum dot patterning, has good film thickness uniformity and high resolution, and solves the problem of reduced luminous efficiency caused by reduced conductivity due to the addition of resin as an adhesive to traditional quantum dot photoresist materials.

[0009] Preferably, the thioxanthone group comprises:

[0010] a keto group; and,

[0011] a benzene ring, connected to the keto group,

[0012] Wherein, the benzene ring is modified with at least one electron-donating group.

[0013] Preferably, the thioxanthone group has a structure as shown in Formula I:

[0014]

[0015] in, represents the connection site of the thioxanthone group, and the R1 and the R2 are each independently selected from the electron donating group.

[0016] In the present invention, the benzene ring structure of the thioxanthone group contains an electron-donating group, which can increase the selection range of the exposure wavelength. The quantum dot material can be exposed at a larger wavelength, reducing the damage of short-wavelength light to the quantum dot material.

[0017] Preferably, the electron donating group includes any one of an amino group, an alkoxy group having 1-5 (eg, 1, 2, 3, 4, or 5) carbon atoms, or an alkyl group having 1-5 (eg, 1, 2, 3, 4, or 5) carbon atoms.

[0018] Preferably, the electron donating group includes any one of amino, methyl, methoxy or tert-butyl.

[0019] Preferably, the quantum dot material further comprises:

[0020] an alkyl chain connected to the thioxanthone group;

[0021] The coordination group is connected to the alkyl chain and is connected to at least one of the first quantum dot entity and the second quantum dot entity.

[0022] Preferably, the coordination group includes any one of a thiol group, a carboxyl group or an amino group.

[0023] It should be noted that the present invention does not impose any special restrictions on the number of carbon atoms and the chain structure of the alkylene chain, and those skilled in the art may adjust them according to actual conditions.

[0024] Illustratively, the alkyl chain includes any one of an alkyl chain with 1 carbon atom, an alkyl chain with 2 carbon atoms, an alkyl chain with 3 carbon atoms, an alkyl chain with 4 carbon atoms, or an alkyl chain with 5 carbon atoms.

[0025] Preferably, the total molar amount of the thioxanthone group and the oleic acid ligand is a first molar amount, the thioxanthone group has a second molar amount, and the ratio of the second molar amount to the first molar amount is any value between 0.2 and 0.6, for example, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55 or 0.6, etc.

[0026] In the present invention, the ratio of the second molar amount to the first molar amount determines the electrical properties of the surface sites of the quantum dot material, determines the cross-linking efficiency, and affects the retention rate of the quantum dot film formed by the quantum dot material during the preparation of the quantum dot pattern. If the molar percentage of the thioxanthone group is too low or too high, the cross-linking effect will deteriorate and the retention rate will be low.

[0027] In a second aspect, the present invention provides a quantum dot patterning method, the quantum dot patterning method comprising:

[0028] Provided is a quantum dot material as described in the first aspect.

[0029] A quantum dot solution is obtained based on the quantum dot material.

[0030] The quantum dot solution is deposited on a substrate to form a quantum dot film, wherein the substrate includes a retention area and a non-retention area.

[0031] The quantum dot film located in the reserved area is irradiated with ultraviolet light, so that the first quantum dot body and the second quantum dot body in the reserved area undergo a cross-linking reaction with the oleic acid ligand through the photosensitive group.

[0032] The quantum dot film in the non-retained area is removed to obtain a patterned quantum dot film.

[0033] Preferably, the wavelength of the ultraviolet light is any value between 365 nanometers and 405 nanometers, for example, 365 nm, 370 nm, 375 nm, 380 nm, 390 nm, 395 nm, 400 nm or 405 nm.

[0034] In the present invention, under ultraviolet light irradiation, adjacent quantum dot bodies are cross-linked through the reaction of thioxanthone groups and oleic acid to form a stable quantum dot film, so that the quantum dot film in the retained area is not easy to be removed, while the quantum dot film in the unretained area is not irradiated with ultraviolet light, and the adjacent quantum dot bodies are not cross-linked, so it is easy to be removed. The wavelength of the ultraviolet light used is any value between 365 nanometers and 405 nanometers, and the luminescent wavelength is longer, which can reduce the damage of short-wavelength light to the quantum dots.

[0035] In a third aspect, the present invention provides a quantum dot light-emitting device, comprising a substrate, an anode, a light-emitting layer and a cathode stacked in sequence on the substrate, the light-emitting layer comprising a quantum dot film layer, and the quantum dot film layer is prepared by the quantum dot patterning method as described in the second aspect.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] In the present invention, the quantum dot material comprises a first quantum dot body, a second quantum dot body, an oleic acid ligand and a photosensitive group, wherein the photosensitive group is a thioxanthone group, and the quantum dot material can realize direct photolithography. When the quantum dot material provided by the present invention is used for quantum dot patterning, the thioxanthone group undergoes hydrogen extraction in the ultraviolet irradiation area, and undergoes hydrogen insertion reaction with the oleic acid ligand to realize cross-linking of adjacent quantum dot bodies, thereby forming a stable quantum dot film, and the quantum dot film prepared by the quantum dot material has good film thickness uniformity. The quantum dot material can realize quantum dot patterning while ensuring high pixel density, and can achieve the effect of full-color display. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 A schematic diagram of a cross-linking reaction of a quantum dot material of Formula 2 when exposed to light in one embodiment of the present invention;

[0039] Figure 2 This is a schematic diagram of the cross-linking reaction of the quantum dot material of Formula 3 when exposed to light in another embodiment of the present invention;

[0040] Figure 3 This is a schematic diagram of a cross-linking reaction of the quantum dot material of Formula 4 when exposed to light in another embodiment of the present invention;

[0041] The dotted line represents the coordination connection between the coordination group and the quantum dot, QD represents the quantum dot itself, Figure 1-3 Only one or two ligand molecules are shown on the quantum dot body for illustration, and the remaining ligand molecules are omitted and not shown. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0043] Unless otherwise defined, the technical terms or scientific terms used in the present disclosure should be understood by people with ordinary skills in the field to which the present disclosure belongs. The "first", "second" and similar words used in the present disclosure do not indicate any order, quantity or importance, but are only used to distinguish different components. "Include" or "comprise" and similar words mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but can include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0044] In order to keep the following description of the embodiments of the present disclosure clear and concise, the present disclosure omits detailed descriptions of well-known functions and well-known components.

[0045] An embodiment of the present invention provides a quantum dot material, the quantum dot material comprising a first quantum dot body, a second quantum dot body, an oleic acid ligand and a photosensitive group, wherein:

[0046] The oleic acid ligand is connected to the first quantum dot body and / or the second quantum dot body, the photosensitive group is connected to the first quantum dot body and / or the second quantum dot body, the first quantum dot body and the second quantum dot body are respectively connected to at least one of the oleic acid ligand and the photosensitive group, and the photosensitive group is a thioxanthone group.

[0047] In a possible implementation, the first quantum dot entity is connected to an oleic acid ligand, and the second quantum dot entity is connected to a photosensitive group.

[0048] In a possible implementation, the first quantum dot body is connected to an oleic acid ligand and a photosensitive group, and the second quantum dot body is connected to a photosensitive group.

[0049] In a possible implementation, both the first quantum dot body and the second quantum dot body are connected to an oleic acid ligand and a photosensitive group.

[0050] In a possible implementation, the first quantum dot entity is connected to an oleic acid ligand and a photosensitive group, and the second quantum dot entity is connected to an oleic acid ligand.

[0051] The morphology and thickness uniformity of the quantum dot film prepared by the inkjet printing process in the prior art are poor. Due to the limitation of the equipment process size, the pixel density (Pixels Per Inch, PPI) of the printing process is about 230dpi, and the resolution is limited. The use of photolithography technology to prepare quantum dot film can achieve high resolution. The quantum dot photoresist used in the preparation of quantum dot film by photolithography technology usually includes an adhesive and quantum dots dispersed in the adhesive. In order to avoid agglomeration, the proportion of quantum dots in the quantum dot photoresist is usually not high, and the low conductivity leads to low luminescence efficiency. In addition, quantum dots are easy to fall off during the patterning process, and the formed pattern is irregular, which affects the thickness uniformity and optical properties of the quantum dot film.

[0052] In the present invention, the quantum dot material includes a thioxanthone group, which is a photosensitive group, so that the quantum dot film prepared by using the quantum dot material can be photolithographically processed; the thioxanthone group can undergo hydrogen extraction under light, and undergo hydrogen insertion reaction with the oleic acid ligand group connected to the quantum dot, so as to achieve cross-linking of adjacent quantum dot bodies. Due to the occurrence of cross-linking, the quantum dot material is evenly and stably distributed on the substrate, and a stable quantum dot film is formed by photolithography without adding resin as an adhesive, and the film thickness uniformity is good and the resolution is high, thereby solving the problem of reduced luminous efficiency caused by reduced conductivity due to the addition of resin as an adhesive to traditional quantum dot photoresist materials.

[0053] In one possible embodiment, the thioxanthone group includes:

[0054] a keto group; and,

[0055] a benzene ring, connected to the keto group,

[0056] Wherein, the benzene ring is modified with at least one electron-donating group. In a possible embodiment, the thioxanthone group has a structure as shown in Formula 1:

[0057]

[0058] in, represents the connection site of the thioxanthone group, and the R1 and the R2 are each independently selected from the electron donating group.

[0059] In the present invention, the benzene ring structure of the thioxanthone group contains an electron-donating group, which can increase the selection range of the exposure wavelength. The quantum dot material can be exposed at a larger wavelength, reducing the damage of short-wavelength light to the quantum dot material.

[0060] In one possible embodiment, the electron donating group includes any one of an amino group, an alkoxy group having 1-5 carbon atoms (eg, 1, 2, 3, 4, or 5), or an alkyl group having 1-5 carbon atoms (eg, 1, 2, 3, 4, or 5).

[0061] In a possible implementation, the electron donating group includes any one of an amino group, a methyl group, a methoxy group or a tert-butyl group.

[0062] In a possible implementation, the quantum dot material further includes:

[0063] an alkyl chain connected to the thioxanthone group;

[0064] The coordination group is connected to the alkyl chain and is connected to at least one of the first quantum dot entity and the second quantum dot entity.

[0065] In a possible implementation, the coordination group includes any one of a thiol group, a carboxyl group or an amino group.

[0066] It should be noted that the present invention does not impose any special restrictions on the number of carbon atoms and the chain structure of the alkyl chain, and those skilled in the art may adjust them according to actual conditions.

[0067] In a possible embodiment, the alkyl chain includes any one of an alkyl chain with 1 carbon atom, an alkyl chain with 2 carbon atoms, an alkyl chain with 3 carbon atoms, an alkyl chain with 4 carbon atoms, or an alkyl chain with 5 carbon atoms.

[0068] In one possible embodiment, the total molar amount of the thioxanthone group and the oleic acid ligand is a first molar amount, the thioxanthone group has a second molar amount, and the ratio of the second molar amount to the first molar amount is any value between 0.2 and 0.6, for example, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55 or 0.6, etc.

[0069] In the present invention, the ratio of the second molar amount to the first molar amount determines the electrical properties of the surface sites of the quantum dot material, determines the cross-linking efficiency, and affects the retention rate of the quantum dot film formed by the quantum dot material during the preparation of the quantum dot pattern. If the molar percentage of the thioxanthone group is too low or too high, the cross-linking effect will deteriorate and the retention rate will be low.

[0070] An embodiment of the present invention further provides a quantum dot patterning method, the quantum dot patterning method comprising:

[0071] A quantum dot material as described above is provided.

[0072] A quantum dot solution is obtained based on the quantum dot material.

[0073] The quantum dot solution is deposited on a substrate to form a quantum dot film, wherein the substrate includes a retention area and a non-retention area.

[0074] The quantum dot film located in the reserved area is irradiated with ultraviolet light, so that the first quantum dot body and the second quantum dot body in the reserved area undergo a cross-linking reaction with the oleic acid ligand through the photosensitive group.

[0075] The quantum dot film in the non-retained area is removed to obtain a patterned quantum dot film.

[0076] In a possible implementation, the wavelength of the ultraviolet light is any value between 365 nanometers and 405 nanometers, for example, 365 nm, 370 nm, 375 nm, 380 nm, 390 nm, 395 nm, 400 nm or 405 nm.

[0077] In the present invention, under ultraviolet light irradiation, the adjacent quantum dot bodies are cross-linked through the reaction of thioxanthone groups and oleic acid to form a stable quantum dot film, so that the quantum dot film in the retained area is not easy to be removed, while the quantum dot film in the unretained area is not irradiated with ultraviolet light, and the adjacent quantum dot bodies are not cross-linked, so it is easy to be removed. The wavelength of the ultraviolet light used is any value between 365 nanometers and 405 nanometers, and the luminescent wavelength is longer, which can reduce the damage of short-wavelength light to the quantum dots.

[0078] In a possible implementation, when the quantum dot film in the retained area is irradiated with ultraviolet light, a mask plate may be used to shield the quantum dot film in the non-retained area.

[0079] In a possible implementation, a good solvent for quantum dots may be used to wash away the quantum dot film in the unretained area, and the good solvent for quantum dots may be selected from toluene and / or chloroform.

[0080] An embodiment of the present invention also provides a quantum dot light-emitting device, which includes a substrate, an anode, a light-emitting layer and a cathode stacked in sequence on the substrate, the light-emitting layer includes a quantum dot film layer, and the quantum dot film layer is made by the quantum dot patterning method of the above embodiment.

[0081] The beneficial effects of the embodiments of the present invention are as follows: the quantum dot material includes a first quantum dot body, a second quantum dot body, an oleic acid ligand and a photosensitive group, the photosensitive group is a thioxanthone group, the quantum dot material can realize direct photolithography, when the quantum dot material provided by the present invention is used for quantum dot patterning, the thioxanthone group undergoes hydrogen extraction in the ultraviolet light irradiation area, and undergoes hydrogen insertion reaction with the oleic acid ligand to realize cross-linking of adjacent quantum dot bodies, thereby forming a stable quantum dot film, and the quantum dot film prepared by the quantum dot material has good film thickness uniformity. The quantum dot material can realize quantum dot patterning while ensuring high pixel density, and can achieve the effect of full-color display.

[0082] The quantum dot body in this embodiment includes, but is not limited to, any one of cadmium sulfide, cadmium selenide, cadmium zinc, indium phosphide or lead sulfide, or a combination of at least two thereof.

[0083] The present invention will be further described below in conjunction with specific examples, but the present invention is not limited to the following examples.

[0084] In one embodiment, the present invention provides a quantum dot material, which includes a first quantum dot body, a second quantum dot body, an oleic acid ligand and a thioxanthone group, and the first quantum dot body and the second quantum dot body are both connected to the oleic acid ligand and the thioxanthone group.

[0085] The thioxanthone group has the structure shown below:

[0086]

[0087] in, Represents the attachment site of the group.

[0088] The quantum dot material further comprises: an alkyl chain with 4 carbon atoms and a mercapto group, the alkyl chain with 4 carbon atoms is connected to the thioxanthone group, and the mercapto group is connected to the alkyl chain with 4 carbon atoms.

[0089] The oleic acid ligand and thioxanthone group connected to the first quantum dot body in the quantum dot material are the same as the oleic acid ligand and thioxanthone group connected to the second quantum dot body, and both the first quantum dot body and the second quantum dot body are cadmium sulfide (CdS).

[0090] The quantum dot material is shown in Formula 2:

[0091]

[0092] The total molar amount of the thioxanthone group and the oleic acid ligand is a first molar amount, the thioxanthone group has a second molar amount, and a ratio of the second molar amount to the first molar amount is 0.2.

[0093] The ratio of the mass of the first quantum dot body and the second quantum dot body to the mass of the oleic acid ligand is 1:9.

[0094] The solution of the above quantum dot material (the concentration of the quantum dot material is 10 mg / ml) is spin-coated on the substrate (hole transport layer), and the quantum dot material in the retained area is exposed to 365nm ultraviolet light, and then developed and etched to remove the quantum dot material in the unretained area to obtain a quantum dot pattern.

[0095] The beneficial effects of the embodiments of the present invention are as follows: the thioxanthone group can extract hydrogen under light and undergo a hydrogen insertion reaction with the oleic acid ligand, which can cross-link adjacent quantum dot bodies to form a stable quantum dot film. The schematic diagram of the cross-linking reaction is shown in FIG. Figure 1 As shown, the quantum dot film in the retained area is not easy to be removed, while the quantum dot film in the non-retained area has not been irradiated with ultraviolet light, and the adjacent quantum dot materials are not cross-linked, so it is easy to be removed. The quantum dot pattern made using the quantum dot material has a uniform distribution of quantum dot materials, good film thickness uniformity, and high resolution.

[0096] According to the variation of the above embodiment, the only difference is that the ratio of the second molar amount to the first molar amount is 0.1, and the rest is the same as the above embodiment. The cross-linking effect of the quantum dot material is deteriorated, and the retention rate of the formed quantum dot film is reduced.

[0097] According to the variation of the above embodiment, the only difference is that the ratio of the second molar amount to the first molar amount is 0.7, and the rest is the same as the above embodiment. The cross-linking effect of the quantum dot material is deteriorated, and the retention rate of the formed quantum dot film is reduced.

[0098] It can be seen that the quantum dot material with a ratio of the second molar amount to the first molar amount of 0.2-0.6 has better performance.

[0099] In another embodiment, the present invention provides a quantum dot material, including a first quantum dot body, a second quantum dot body, an oleic acid ligand and a thioxanthone group, wherein the first quantum dot body is connected to the thioxanthone group, and the second quantum dot body is connected to the oleic acid ligand.

[0100] The thioxanthone group has the structure shown below:

[0101]

[0102] in, Represents the attachment site of the group.

[0103] The quantum dot material further includes: an alkyl chain with 5 carbon atoms and a mercapto group, wherein the alkyl chain with 5 carbon atoms is connected to the thioxanthone group; and the mercapto group is connected to the alkyl chain with 5 carbon atoms.

[0104] The first quantum dot body and the second quantum dot body are both cadmium selenide (CdSe)

[0105] The quantum dot material is shown in Formula 3.

[0106]

[0107] The total molar amount of the thioxanthone group and the oleic acid ligand is a first molar amount, the thioxanthone group has a second molar amount, and a ratio of the second molar amount to the first molar amount is 0.35.

[0108] The ratio of the total mass of the first quantum dot body and the second quantum dot body to the mass of the oleic acid ligand is 2:8.

[0109] A solution of the above quantum dot material (the concentration of the quantum dot material in the solution is 20 mg / ml) is spin-coated on a substrate (hole transport layer), and the quantum dot material in the retained area is exposed to 380 nm ultraviolet light, and then developed and etched to remove the quantum dot material in the unretained area to obtain a quantum dot pattern.

[0110] The beneficial effects of the embodiments of the present invention are as follows: the thioxanthone group can extract hydrogen under light and undergo a hydrogen insertion reaction with the oleic acid ligand, which can cross-link adjacent quantum dot bodies to form a stable quantum dot film. The schematic diagram of the cross-linking reaction is shown in FIG. Figure 2 As shown, the quantum dot film in the retained area is not easy to be removed, while the quantum dot film in the non-retained area has not been irradiated with ultraviolet light, and the adjacent quantum dot materials are not cross-linked, so it is easy to be removed. The quantum dot pattern made using the quantum dot material has a uniform distribution of quantum dot materials, good film thickness uniformity, and high resolution.

[0111] In another embodiment, the present invention provides a quantum dot material, which includes a first quantum dot body, a second quantum dot body, an oleic acid ligand and a thioxanthone group, wherein the first quantum dot body and the second quantum dot body are both connected to the oleic acid ligand and the thioxanthone group.

[0112] The thioxanthone group has the structure shown below:

[0113]

[0114] in, Represents the attachment site of the group.

[0115] The quantum dot material further includes: an alkyl chain with 5 carbon atoms and an amino group, wherein the alkyl chain with 5 carbon atoms is connected to the thioxanthone group; and the amino group is connected to the alkyl chain with 5 carbon atoms.

[0116] The oleic acid ligand and thioxanthone group connected to the first quantum dot body in the quantum dot material are the same as the oleic acid ligand and thioxanthone group connected to the second quantum dot body, and both the first quantum dot body and the second quantum dot body are cadmium sulfide (CdS).

[0117] The quantum dot material is shown in Formula 4.

[0118]

[0119] The total molar amount of the thioxanthone group and the oleic acid ligand is a first molar amount, the thioxanthone group has a second molar amount, and a ratio of the second molar amount to the first molar amount is 0.6.

[0120] The ratio of the mass of the first quantum dot body and the second quantum dot body to the mass of the oleic acid ligand is 3:7.

[0121] The solution of the above quantum dot material (the concentration of the quantum dot material is 30 mg / ml) is spin-coated on the substrate (hole transport layer), and the quantum dot material in the retained area is exposed to 405 nm ultraviolet light, and then developed and etched to remove the quantum dot material in the unretained area to obtain a quantum dot pattern.

[0122] The beneficial effects of the embodiments of the present invention are as follows: the thioxanthone group can extract hydrogen under light and undergo hydrogen insertion reaction with the oleic acid ligand, which can cross-link adjacent quantum dot bodies to form a stable quantum dot film. The schematic diagram of the cross-linking reaction principle is shown in FIG. Figure 3 As shown, the quantum dot film in the retained area is not easy to be removed, while the quantum dot film in the non-retained area has not been irradiated with ultraviolet light, and the adjacent quantum dot materials are not cross-linked, so it is easy to be removed. The quantum dot pattern made using the quantum dot material has a uniform distribution of quantum dot materials, good film thickness uniformity, and high resolution.

[0123] It should be noted that Figure 1-Figure 3 In order to clearly indicate the specific reaction position, only a part of the structure and its cross-linking reaction are schematically illustrated, and the present invention is not limited thereto.

[0124] According to the variation of the above embodiment, the only difference is that the quantum dot material does not include oleic acid ligands, and the rest is the same as the above embodiment, and the quantum dot material cannot be cross-linked.

[0125] According to the variation of the above embodiment, the only difference is that the quantum dot material does not include a thioxanthone group, and the rest is the same as the above embodiment, and the quantum dot material cannot be cross-linked.

[0126] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A quantum dot material, characterized in that: The quantum dot material comprises a first quantum dot body, a second quantum dot body, an oleic acid ligand and a photosensitive group, wherein: The oleic acid ligand is connected to the first quantum dot body and / or the second quantum dot body, the photosensitive group is connected to the first quantum dot body and / or the second quantum dot body, the first quantum dot body and the second quantum dot body are respectively connected to at least one of the oleic acid ligand and the photosensitive group, and the photosensitive group is a thioxanthone group.

2. The quantum dot material according to claim 1, characterized in that The thioxanthone groups include: a keto group; and, a benzene ring connected to the keto group; Wherein, the benzene ring is modified with at least one electron-donating group.

3. The quantum dot material according to claim 2, characterized in that: The thioxanthone group has a structure as shown in Formula 1: in, represents the connection site of the thioxanthone group, and the R1 and the R2 are each independently selected from the electron donating group.

4. The quantum dot material according to claim 2, characterized in that: The electron donating group includes any one of an amino group, an alkoxy group having 1 to 5 carbon atoms, or an alkyl group having 1 to 5 carbon atoms.

5. The quantum dot material according to claim 4, characterized in that: The electron donating group includes any one of an amino group, a methyl group, a methoxy group or a tert-butyl group.

6. The quantum dot material according to claim 1, characterized in that: The quantum dot material also includes: an alkyl chain connected to the thioxanthone group; A coordination group connected to the alkyl chain and connected to at least one of the first quantum dot entity and the second quantum dot entity; The coordination group includes any one of a thiol group, a carboxyl group or an amino group.

7. The quantum dot material according to claim 1, characterized in that: The total molar amount of the thioxanthone group and the oleic acid ligand is a first molar amount, the thioxanthone group has a second molar amount, and a ratio of the second molar amount to the first molar amount is any value from 0.2 to 0.

6.

8. A quantum dot patterning method, characterized in that: The quantum dot patterning method comprises: Providing a quantum dot material as described in any one of claims 1-7; Obtaining a quantum dot solution based on the quantum dot material; Depositing the quantum dot solution on a substrate to form a quantum dot film, wherein the substrate includes a retention area and a non-retention area; The quantum dot film located in the reserved area is irradiated with ultraviolet light, so that the first quantum dot body and the second quantum dot body in the reserved area undergo a cross-linking reaction with the oleic acid ligand through the photosensitive group; The quantum dot film in the non-retained area is removed to obtain a patterned quantum dot film.

9. The quantum dot patterning method according to claim 8, characterized in that: The wavelength of the ultraviolet light is any value between 365 nanometers and 405 nanometers.

10. A quantum dot light-emitting device, characterized in that: The quantum dot light-emitting device includes a substrate, an anode, a light-emitting layer and a cathode sequentially stacked on the substrate, the light-emitting layer includes a quantum dot film layer, and the quantum dot film layer is made by the quantum dot patterning method according to claim 8 or 9.